Development of hip dysplasia in hereditary multiple exostosis (2001)
In approximately 25% of patients with hereditary multiple exostosis, there is an abnormal osteochondral formation localized in the femoral proximal metaphysis. This formation often causes a mechanically progressive insufficiency of the acetabular cavity, a true developmental hip dysplasia, that together with a coxa valga deformity, which is also present, causes a gradual deterioration in the relations of this joint. This malformation has a poor prognosis and is difficult to manage. Although this entity is rather frequent and quite severe, it is rarely found in the medical literature. The author describes six private cases, taken from a total of 24,000 patients (0.25/1000) as examples of this entity, and provides a review of the literature.